Legal Protection of the Penataran Temple Site in Blitar Regency in the Digital Era Based on the Utilization of Artificial Intelligence - Prasetyo, Ngesti Dwi; Fadli, Moh; Susilo, Edi; Puspitawati, Dhiana; Lutfi, Mustafa (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
Penataran Temple, a cultural heritage site in Blitar Regency, stands as a testament to the pinnacle of past Nusantara civilization. Despite its significance, the protection of Penataran Temple requires optimization. This study aims to develop a legal protection strategy for Penataran Temple through the use of Artificial Intelligence. Employing statutory, conceptual, and historical approaches, this empirical juridical research analyzes data using sociological juridical methods. The study underscores the urgent need to enhance legal protection, particularly in rebranding the ecotourism potential of Penataran Temple. This effort seeks to cultivate, reaffirm, and revive the noble values of cultural heritage, establishing it as a distinctive landmark enriched by the unique mosaic of local wisdom. Utilizing innovative design and advanced technologies such as artificial intelligence, this approach significantly enhances branding rooted in local wisdom and ancestral heritage. It is crucial for promoting and safeguarding the temple from legal exploitation by parties lacking integrity and historical awareness in the digital age.